Prevalencia De Parasitosis Intestinales Y Su Posible Relaciòn Con Estados Anèmicos En Los Niños Que Acuden A Los Centros De Educaciòn Inicial - Cando Brito, Verónica Mercedes; Escobar Arrieta, Sandra Noemí; Espinoza Chávez, Carlos Eduardo; Caluña Sánchez, Edmundo Rodrigo (European Scientific Journal, ESJ, 2017)
The purpose of this current research is to determine the parasites which has the highest prevalence in the children population in regards to anemia problems in boys and girls aged from 3 to 5 years. The study sample was chosen at random. It was represented by 600 boys and girls from the initial education centers of Riobamba-Chambo district located in Ecuador. From these children, it was possible to obtain 600 stool samples and 600 blood samples that were processed through the fresco technique with lugol and saline solution at 0.85% as well as an automated hematic biometry. The result shows that the total population with parasites was 44,7%. Boys represent the highest parasite prevalence with 51,5% related to the girls with 48,5%. The most frequent parasites were: Entamoeba coli (53,18%), Giardia Lambia (18,15%), Histolytic Entamoeba (14,01%), Endolimax nana (5,42%), lodamoeba butschlii (3,50%), Chilomastix mesnili (3,18%), Hymenolepis nana (1,91), and Ascaris lumbricoides (0,65%). It was concluded that there are no significant relationship between the anemic states and the intestinal parasites on boys and girls since the percentage was 4,5%. It was suggested to the principal of the Riobamba - Chambo District of the Ministry of Education to carry out promotion, prevention, and health care campaigns directed towards the authorities and teachers of the Initial Education Centers as well as parents and their children in order to improve the hygiene and food safety habits of students.